Peramalan Hasil Panen Mangga dengan Pendekatan Seasonal Autoregresif Integrated Moving Average Method - Willy Estuhardini Ersa Muthahar; Wellie Sulistijanti (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Mango is one of the agricultural products in Indramayu large enough.This arises from a number of farmers who cultivate this fruit, and the public interestis high enough to consume this fruit. The data studied from 2003 until 2015.Given the plot of data generated, the data has a seasonal pattern of eachperiod. This research is done by using SARIMA method (SeasonalAutoregressive Moving Average). From the results of forecasting methodsSARIMA models Box-Jenkins ARIMA produce (1,1,1) (1,1,0) =42) with the equation.From this research obtained by forecasting yields all kinds of mangoes in 20162017 in Indramayu district with the highest prediction results obtained inOctober-December 2017 and the lowest padabulan January-March 2016  Keywords: Forecasting, Harvest Mango, SARIMA